2014
DOI: 10.1155/2014/761582
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Asymptomatic Short Sternum in a Healthy Young Girl

Abstract: Congenital sternal defects are rare deformities frequently associated with other anomalies of the chest wall and other organ systems. Although pectus excavatum, pectus carinatum, and cleft sternum can present as isolated deformity, in most cases they are associated with heart and inner organs anomalies and described as symptoms of syndromes like Marfan syndrome, Noonan syndrome, Poland anomaly, and Cantrell pentalogy. In contrast, the etiology of an isolated defect is not well understood. We observed a short s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Even different primary rib anomalies may cause a deformity of the chest wall; however, an attentive clinical examination is sufficient for a differential diagnosis. Sternal defects are also frequent in rare genetic syndromes, such as Noonan syndrome, trisomy 17, and trisomy 18, in which they occur as a large spectrum of anomalies (sternal deformity in a shield chest, short sternum with a cleft, delayed sternal ossification) associated with other musculoskeletal malformations [17] , [19] , [20] ( Table 1 , Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even different primary rib anomalies may cause a deformity of the chest wall; however, an attentive clinical examination is sufficient for a differential diagnosis. Sternal defects are also frequent in rare genetic syndromes, such as Noonan syndrome, trisomy 17, and trisomy 18, in which they occur as a large spectrum of anomalies (sternal deformity in a shield chest, short sternum with a cleft, delayed sternal ossification) associated with other musculoskeletal malformations [17] , [19] , [20] ( Table 1 , Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…No treatment was necessary as she was asymptomatic. 7 Another paleontological case report of relevance is the anomaly of Santa Rosa de Viterbo, an Italian mummy. A careful study of the well-preserved body had revealed isolated total agenesis of the sternum without any other identifiable abnormality.…”
Section: A B C D E F Figure 4: Mri Thorax Of the Patient T2w Axial Smentioning
confidence: 99%